Experiences of professional nurses regarding shortage of resources at a tertiary hospital in Gauteng Province, South Africa: qualitative study - Jiyane, Makoasha Philistus; Khunou, Sisinyana Hannah (Jurnal Ners, 2023)
Background: Shortage of resources in hospitals is a global problem with South Africa not being excluded. These leads to a situation where most health care workers especially professional nurses (PNs)  leave the health institutions to private hospitals or abroad for better opportunities. The study explored and described professional nurses' experiences regarding shortage of resources at a tertiary hospital in Gauteng Province. Methods: Qualitative, explorative, descriptive design was used on a sample of 16 professional nurses (PNs), who have worked for two or more years in selected units. Unstructured individual conversations with a grand tour question were used. Tesch's method was employed to analyze data. Results: The study revealed both negative and positive experiences regarding the deficiency of resources. PNs experienced the following: The study revealed four themes: 1) Experiences pertaining to lack of material resources; 2)Negative impact of a shortage of resources on patients; 3) Experiences on inadequate number of nurses and support staff; 4) Dealing with a shortage of resources Conclusions: Appropriate measures should be put in place to ensure that resources are adequate at this tertiary hospital. Medical machinery should be audited monthly and a daily checklist used to document available stock. Appropriate recruitment and retention policies must be implemented by the Human Resource Department to ensure that vacant posts are filled timeously and reduce high staff turnover. Perceptions of patients could be explored related to the unavailability of medicine in healthcare facilities